THE EFFECT OF ROOT GAP ON BENDING TEST USING FCAW WELDING ON SS 400 STEEL MATERIALS AT 3G POSITION - Nuzulul Arif; Erifive Pranatal; Iftika Philo Wardhani; Renanda Bayu Harsi (Journal of Applied Sciences, Management and Engineering Technology, 2022)
This study aims to analyze the effect of the root gap on bending test of SS 400 steel materials with different thicknesses of 10 mm and 12 mm using FCAW (Flux Core Arc Welding) welding in the 3G Vertical up position without backing ceramic. This study uses quantitative method, and the standard used in the test is ASME section IX (2019). The results of the study concluded that in specimens within the thickness of 10 mm, the highest value was obtained at the root gap variation of 4.4 mm with a bending stress value of: 467.48 MPa. Then on the specimen with a thickness of 12 mm, the highest value was found in a variation of 3 mm with a bending stress value of: 805.37 MPa